SOSIALISASI PENGENDALIAN HAMA DAN PENYAKIT TANAMAN CABAI DI DESA KWANG RUNDUN KABUPATEN LOMBOK TIMUR - Aufa Harman, Carlen; Armini, Armini; Januardo, Bryan; Ainun, Muh; Handayani, Ayudina; Nadia, Nadia; Aditya Prayoga, Muhammad; Nadiva Alivia, Baiq; Aini, Qurrotul; Anggun Nadila, Fuji; Wahyu Wiriasto, Giri (Universitas Mataram, 2025)
Chilli is one of the most widely cultivated crops in the NTB region, including in Kwang Rundun Village, East Lombok Regency. Farmers' understanding of pest and disease control is needed to improve the quality, quantity and production of chilli. The socialisation of pest and disease control in chilli plants is a form of student contribution in introducing and providing an understanding of pest and disease control in chilli plants. The method of activities carried out in community service has three stages, namely the observation stage, the discussion stage, and the socialisation stage. The farmers gained a thorough understanding of chilli cultivation starting from the seed selection process, how to control pests and diseases to the harvest process. It is hoped that socialisation activities can be held again with different types of cultivated plants because farmers in Kwang Rundun Village do not only cultivate chilli plants.